1994
DOI: 10.1139/y94-172
|View full text |Cite
|
Sign up to set email alerts
|

Gastric inhibitory polypeptide and glucagon-like peptide-1(7–36) amide exert similar effects on somatostatin secretion but opposite effects on gastrin secretion from the rat stomach

Abstract: Previous studies on the isolated perfused stomach have shown that gastric inhibitory polypeptide (GIP) and glucagon-like peptide-1(7-36) amide (GLP-1(7-36) amide) stimulate release of somatostatin (somatostatin-like immunoreactivity, SLI). GIP produced a paradoxical increase in gastrin secretion, whereas GLP-1(7-36) was inhibitory. In the current study, the actions of synthetic (sp) and native (np) porcine and synthetic human (sh) GIP, GLP-1(7-36), and GLP-1(7-37) on SLI and gastrin secretion were compared usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…was not carried out, but preliminary data suggest that acute as well as subchronic peripheral administration of NN2211 reduces meal size similar to what is known for other gastrointestinal hormones, such as CCK (22,23; P.J.L., unpublished observations). It has been suggested that signals that modify food intake via diminishing meal size are both direct and indirect (23).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…was not carried out, but preliminary data suggest that acute as well as subchronic peripheral administration of NN2211 reduces meal size similar to what is known for other gastrointestinal hormones, such as CCK (22,23; P.J.L., unpublished observations). It has been suggested that signals that modify food intake via diminishing meal size are both direct and indirect (23).…”
Section: Discussionmentioning
confidence: 78%
“…Thus, it seems likely that the anorectic effect of peripheral GLP-1 is mediated via a peripherally accessible site located either in the brainstem or on vagal afferents. In rats, the inhibitory actions of GLP-1 on gastric motility is mediated via the vagus nerve (11), but also direct inhibition of gastrin secretion as well as stimulation of somatostatin release may affect gastric emptying (21,22). Obviously, delayed gastric emptying coun- teracts excessive meal-related glucose excursions with consequent beneficial glucose homeostatic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Because direct arterial infusion of GLP-1 did not inhibit antral or pyloric motor activity in dogs, a direct effect of GLP-1 on gastric smooth muscle seems unlikely (6). Although GLP-1 can release somatostatin (24), which increases fasting gastric volume (13), the inhibitory effect of GLP-1 on fasting small bowel motility is not mediated by somatostatin (46). In rats, GLP-1 increases blood pressure and heart rate and reduces intestinal motility via sympathetic stimulation (50,51).…”
Section: Discussionmentioning
confidence: 96%
“…This research was presented in abstract form at the American Motility Society Meeting, Santa Monica, CA, September [22][23][24][25] 2005. …”
Section: Acknowledgmentsmentioning
confidence: 99%
“…GIP 1-42 is known to promote somatostatin release from the stomach (15,24,26). To determine whether amidated GIP has similar potency as GIP , we performed an in situ perfusion study using a vascularly perfused isolated mouse stomach preparation.…”
Section: Furin Is Likely Not Involved In Pro-gip Processingmentioning
confidence: 99%